Teleproctoring of endovascular treatment of aortic diseases in times of pandemic and war - Oliveira, Fabio Augusto Cypreste; Campedelli, Fabio Lemos; De Souza Amorelli, Carlos Eduardo; Da Silva Pozzetti, Ana Luiza Pereira [UNESP]; Dos Santos Bossa, Milena Fachini; João, Priscila Cristina (FapUNIFESP (SciELO), 2025)
Telemedicine encompasses various activities leveraging technology for remote health care. Surgical teleproctoring is described in the literature and has been used by some medical specialties for real-time and remote intraoperative guidance. However, there is still limited evidence on its use for the implantation of aortic endoprostheses. Technological progress and the advancement of telemedicine encourage surgical telementoring, especially in circumstances where in-person proctorship is not feasible, such as in remote areas, during pandemics and wars, and in settings lacking financial resources. In this context, we present the successful application of easily available and low-cost online teleproctoring of real-time aortic endoprosthesis implantation, addressing aortic diseases in a country experiencing social isolation due to the ongoing pandemic and war.
Teleproctoria no tratamento endovascular de doenças aórticas em tempos de pandemia e guerra
Keywords: aorta; covid-19; endovascular procedures; telemedicine; telementoring; teleproctoring; war